The Effect of Young Timor Deer (Rusa timorensis) Hornbill Flour Supplementation on the Testicular Size of Male Wistar Rats (Rattus norvegicus) - Kartika, Nur Hafidzah Devi; Samsudewa, Daud; Prasetya, Nor Basid Adiwibawa; Nandhirabrata, Raditya (Bantara Journal of Animal Science, 2025)
The processing of young deer antlers exemplifies the use of deer as wildlife, guided by the principle of continuity and without harming them. The purpose of this study was to determine the effect of young Timor deer antler meal and to determine the impact of its supplementation on the size of the testes of male Wistar rats. Twenty male Wistar rats with a body weight of 200–250 g and an age of 90 days were used. The samples were divided into four groups: a control group and three treatment groups of young Timor deer antler meal at doses of 25 mg kg-1 BW-1, 50 mg kg-1 BW-1, and 100 mg kg-1 BW-1. Ca and Zn measurements were carried out using an atomic absorption spectrophotometer at the Feed Nutrition Laboratory of Diponegoro University. The size of the left and right testes (length, width, diameter, and weight) was analyzed using Analysis of Variance, and Duncan's Multiple-Range Test was used for testis weight. Data on Ca and Zn content were analyzed descriptively. Therefore, it can be concluded that supplementation with young Timor deer antler flour affected testicular weight, but not testicular length, width, and diameter. The results showed a significant difference (P<0.05) in testicular weight parameters, and testicular length, width, and diameter were not significantly different. Therefore, it can be concluded that supplementation with young Timor deer antler flour affected testicular weight, but not testicular length, width, and diameter.